A efetividade de grupos de pais para o tratamento de problemas internalizantes e o papel do comportamento do supervisor na formação de terapeutas analítico-comportamentais - Tozze, Karina Ferraz [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
A supervisão de estágio é um processo de ensino e de aprendizagem que visa gerar mudanças no comportamento do estagiário/terapeuta, a fim de facilitar a prática clínica do futuro psicólogo. Diante disso, a presente pesquisa foi dividida em dois estudos complementares. O primeiro estudo buscou apresentar dados referentes a uma intervenção realizada por terapeutas com pais que se queixavam de problemas de comportamentos internalizantes dos filhos. Foram feitas aplicações de instrumentos nos pais para avaliar a efetividade dos atendimentos e analises dos dados referentes ao processo terapêutico, por meio da descrição da interação terapêutica. O que se obteve nesse estudo, foi de que os pais, após a intervenção, reduziram as queixas levantadas antes dos atendimentos. A interação terapêutica se mostrou como uma ferramenta importante que contribuiu para a melhora dos clientes. Pretendeu-se compreender melhor o processo de supervisão de estágio e se a supervisão era uma variável a ser considerada diante dos dados observados no primeiro estudo. A partir da identificação e descrição de categorias comportamentais do supervisor de estágio e de estagiários durante o processo de supervisão oral e escrita. O mesmo estudo também descreveu se as estagiárias aplicaram ou não as recomendações dadas pela supervisora, além de identificar quais foram essas recomendações. Notou-se que as recomendações fornecidas pela supervisora foram seguidas, em sua maior parte, e possibilitaram a aquisição de habilidades terapêuticas por parte das estagiárias, havendo uma contribuição para o fim das queixas trazidas pelos clientes. Ao fim, questões metodológicas e novas possibilidades de pesquisa foram discutidas.

The probation supervision is a process of teaching and learning that aims to generate changes in behavior trainee / therapist in order to facilitate future clinical psychologist practice. About that noted the importance of developing research involving probation supervision for psychological support that are conducted in group form. Therefore, the present reserarch was separed into two complementary studies. The first study aimed to present data relating to an intervention performed by trainees / therapists with parents who complained of problems of internalizing behaviors of their children. So instruments applications were made to parents to evaluate the effectiveness of psychological support. In addition, data on the therapeutic process were analyzed by describing the therapeutic interaction. It has been obtained in this study was that parents after the intervention reduced the complaints raised before the sessions. About the therapeutic interaction that was show as an important tool contributing to the improvement of patients. Then was intended to understand the probation supervision process and supervision was one variable to be considered face of data observed in the first study. This way the second study identified and described behavioral categories of the probation supervisor and trainees during the process of oral and written supervision. The same study also described if the trainees applied or not the recommendations given by the supervisor and identified what were these Recomendations. That way it was observed that the Recommendations provided by the supervisor both reports as in probation supervision environment were followed, for the most part, and made possible the purchase of therapeutic skills by the trainees, That way it was observed that the recommendations provided by the supervisor, both reports as the very probation supervision environment were followed, for the most part and made possible the acquisition of therapeutic skills by the trainees, in the course of probation and so having a contribution to the end of complaints brought by the parents. After methodological issues and new research possibilities were discussed.
The effectiveness of parent groups for the treatment of internalizing problems and the role of the supervisor's behavior in the formation of behavior-analytic therapists
Keywords: Supervisão de estágio; Terapia em grupo; Problemas de comportamento internalizantes; Interação terapêutica; Supervision; Group therapy; Internalizing behavior problems; Therapeutic interaction